ASALAH GAGAL-TUMBUH PADA ANAK BALITA MASIH TINGGI: ADAKAH YANG “KURANG” DALAM KEBIJAKAN PROGRAM GIZI DI INDONESIA? - Jahari, Abas Basuni (GIZI INDONESIA, 2008)
WHAT’S WRONG WITH NUTRITION PROGRAM POLICY? WHY GROWTH FALTERING AMONG UNDER-FIVE CHILDREN REMAINS HIGH? The indicator of nutritional status used in the large scale survey is weight-for-age (W/A) orunderweight indicator. The question is why the prevalence of underweight among children underfives is still high, while the prevalence of overweight tends to increase? This analysis is carried outto find out what is the hidden characteristic of growth faltering among Indonesian children below 5years of age. The analysis used anthropometry data from different sources that collecting bothlength or height and weight dataThe anthropometry data is converted into standardized values(z_score) using WHO-2006 child growth standard. The prevalence of underweight (W/A), stuntingbased on length of height-for-age (H/A) and wasting based on weight-for-length or height (W/H)were calculated based on cut-off points suggested by the WHO child growth standard. Crosstabulation between any pair of two indicators was made to understand the characteristics ofgrowth faltering.The obvious problem in growth faltering among Indonesian under-five children isstunting. The prevalence of stunting is the highest among the prevalence of underweight andwasting. In general it was found that about 85 percent underweight children were also stunted, andaround 80 percent underweight children were having normal weight-for-height (not wasted). Fromthe results of the analysis It is clear that most of the underweight children were stunted and mostof the underweight children had normal weight-for-height. The problem of underweight is stronglyrelated with the problem of stunting. Efforts to reduce the prevalence of underweight should alsotake into account the efforts to reduce problem of stunting. Using weight-for-age (W/A) alone asthe basis of nutrition intervention is not enough, therefore, measuring length or height is stronglyrecommended to understand clearly the characteristics of growth problems among under-fivechildren.KEYWORDS: anthropometry, underweight, stunting, wasting